Kadar Protein, Kadar Albumin, dan Tingkat Kesukaan Brownies Mocaf Ikan Gabus - Asysyifa, Rayyana Aurora Nur; Fitriyanti, Addina Rizky; Sulistyaningrum, Hersanti; Suyanto, Agus (Jurnal Gizi, 2024)
Background: Brownies are generally made from wheat flour, but can be made with local food mocaf flour. Mocaf protein is lower than wheat flour, wheat flour has 8-13% protein while mocaf has 1.2% protein content.   Objectives: The purpose of the study was to determine the addition of snakehead fish to protein levels, albumin levels, and preference test for mocaf brownies.The addition of snakehead fish to mocaf brownies aims to increase protein levels. Snakehead fish contains high protein and albumin,protein of 16.2g/100g and albumin content of 6.224g/100g. Preference test is researched to find out brownies are acceptable to consumers.  Method: The study used the Complete Randomized Design experimental method with the additionof snakehead fish 0%;7.3%;9.6%;11.7%, repetition 6 times. Protein content testing is carried out by the kjeldahl method, albumin levels by the biuret method and preference levels by organoleptic tests. Data analysis of protein levels and albumin levels using the ANOVA one-way test, and analysis of favorability data using the Friedman Test test then proceed to the Wilcoxon test.   Results: The test results of protein levels and albumin levels get a value of p >0.05, namely the addition of snakehead fish does not have a significant effect. The results of the favorability leveltest on color, aroma, taste get a value of p < 0.05 that the addition of snakehead fish has a significant effect and the texture of p > 0.05 is not significant. Test results with the addition of snakehead fish with the highest protein content and albumin content treatment 11.7%, the highest color test at 7.3% and 9.6%, the highest aroma test at 9.6%, the highest taste and texture test at 7.3%.  Keywords : Albumin Levels, Mocaf Brownies, Preference Levels, Protein Levels, Snakehead Fish